Preliminary analysis of trace metals in well water collected from Lehigh Acres, Florida, USA - J.O. Olowoyo; L.G. Pap; O.M. Oladeji (Journal of Trace Elements and Minerals)
Introduction: The supply of water for domestic purposes from wells is common in some areas in the United States of America. However, research has shown that this underground water may become polluted with trace metals due to both natural processes and anthropogenic effects. Objectives: The current study evaluated the levels of trace metals in well water from a community in Florida. The study further investigated the potential health risks associated with the levels of trace metals in the water samples. Results: A total of 34 water samples (treated and untreated) were used for the study. The result showed the presence of Pb in both treated and untreated water samples 18.2 ± 1.8 µg L-1–117.7 ± 4.5 µg L-1. Fe concentrations ranged from 10.7 ± 2.2 µg L-1–940.1 ± 3.5 µg L-1. Values obtained for Pb were higher than the recommended limit. Three of the water samples have Fe values above the recommended limit for human consumption. Differences obtained from the treated and untreated water samples for some of the trace metals were not significant (p < 0.05). The health risk calculated in this study for Pb, and other trace metals did not show any potential health risk at this stage because the values were all <1. The ecological risk assessment also showed no threat to the environment at this stage with a caution for Pb and Cu due to the values obtained. Conclusion: The presence of Pb in water suggests the need for continuous monitoring of the water samples from the area and further investigation to the actual source of Pb may be necessary so as to ensure safety.